An observational cohort study of the effects of septoplasty with or without inferior turbinate reduction in patients with obstructive sleep apnea - Moxness, Mads Henrik Strand (BioMed Central, 2014)
BACKGROUND: The objective of this observational study was to evaluate the outcomes of intranasal surgery in patients with obstructive sleep apnea (OSA) in a single institution in Norway. METHODS: Fifty-nine patients with OSA and clinically significant nasal obstruction underwent either septoplasty alone or septoplasty with concomitant volume reduction of the turbinates from August 2008 until the end of December 2010. Subjects were scheduled for sleep polygraphy before and 3 months after treatment. In this observational single-centre cohort study we evaluated and compared the effect of these two specific surgical procedures on sleep related parameters. RESULTS: There was a significant reduction in the apnea-hypopnea index (AHI) only in the group that had septoplasty with turbinate reduction (17.4, (SD 14.4) – 11.7, (SD 8.2), p <0.01), and this effect was significantly better than in the group treated with septoplasty alone. Other objective parameters remained unchanged. Subjective assessments obtained with a postoperative questionnaire showed an equally positive effect on diurnal sleepiness and nasal obstruction in both groups, and a better effect on sleep quality in the combined treatment group. CONCLUSION: The effect of nasal surgery on obstructive sleep apnea seemed to be greater when there were indications for combined surgery of the inferior turbinates and the nasal septum, compared to when there were indications for septoplasty alone.